The Relationship Between Responses and Motivation Learning on Online Learning of 11th-Grade Students of Vocational High School Wiraswasta Cimahi in Islamic Religious Education Subject - Nurul Firdaus; Asep Herdi; Asep Andi Rahman; Dwi Fitria Al Husaeni (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2023)
At this time, student motivation in learning Islamic Religious Education is still relatively low, especially during the COVID-19 pandemic. Various media were developed to support online learning. However, there are still many students who are indifferent during the learning process. This study aims to determine: (i) the reality of student responses to online learning during the covid-19 pandemic in class XI vocational high school Wiraswasta Cimahi, (ii) the reality of student learning motivation in Islamic religious education subjects in class XI vocational high schoolWiraswasta Cimahi, and (iii)the relationship between student responses to online learning during the COVID-19 pandemic and student motivation in Islamic religious education subjects in class XI vocational high schoolWiraswasta Cimahi. This study uses a quantitative approach with a descriptive method. In this study the sample was taken from 35 students of class XI vocational high schoolWiraswasta Cimahi. Data analysis of the two variables was carried out using statistical methods which were divided into two approaches, namely partial analysis and correlation analysis. Based on the results of the study, it was concluded: (i) the reality of student responses to online learning during the covid-19 pandemic was categorized as positive, at intervals of 3.40 - 4.19 (ii) the reality of their learning motivation in Islamic Religious Education subjects was categorized as good, at intervals 3.40 – 4.19, and (iii) the relationship between students' responses to online learning during the covid-19 pandemic with their learning motivation in Islamic Religious Education subjects is (a) a correlation coefficient of 0.58 including in the medium or medium category . (b) The hypothesis is accepted because t arithmetic is 4.09 greater than t table with (1.69), and (c) The degree of relationship between variable X and variable Y is 34%. Therefore, there is a relationship or influence between student responses to online learning during the COVID-19 pandemic and their learning motivation in Islamic Religious Education subjects